2022
DOI: 10.1111/jopr.13553
|View full text |Cite
|
Sign up to set email alerts
|

Additive Manufacturing of Dental Ceramics: A Systematic Review and Meta‐Analysis

Abstract: The purpose of this systematic review and meta-analysis was to evaluate the effect of using additive manufacturing (AM) for dental ceramic fabrication in comparison with subtractive manufacturing (SM), and to evaluate the effect of the type of AM technology on dental ceramic fabrication. Materials and methods: A search was conducted electronically in MEDLINE (via PubMed), EBSCOhost, Scopus, and Cochran Library databases, and also by other methods (table of contents screening, backward and forward citations, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 70 publications
(331 reference statements)
0
13
1
Order By: Relevance
“…Under the NSA conditions, the HC and 3YZ groups showed lower mean RMS values, whereas the M group showed the highest mean RMS value ( P < 0.05). The mean RMS values of all groups, except the HC and 3YZ groups, exceeded the clinically acceptable limit of 50 μm for the CAD‐CAM crown 51–56 . Under PSA and LSA conditions, no significant difference was observed among the materials.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…Under the NSA conditions, the HC and 3YZ groups showed lower mean RMS values, whereas the M group showed the highest mean RMS value ( P < 0.05). The mean RMS values of all groups, except the HC and 3YZ groups, exceeded the clinically acceptable limit of 50 μm for the CAD‐CAM crown 51–56 . Under PSA and LSA conditions, no significant difference was observed among the materials.…”
Section: Resultsmentioning
confidence: 77%
“…The mean RMS values of all groups, except the HC and 3YZ groups, exceeded the clinically acceptable limit of 50 μm for the CAD-CAM crown. [51][52][53][54][55][56] Under PSA and LSA conditions, no significant difference was observed among the materials. For each restorative material group, the NSA condition showed a significantly higher RMS value than the PSA or LSA condition (P < 0.05), except for the HC and 3YZ groups.…”
Section: Resultsmentioning
confidence: 88%
“…AM zirconia seems to be more sensitive to shrinkage during the sintering process. A review evaluating the AM of dental ceramics reported favorable volumetric shrinkage for SM compared to AM (Al Hamad et al, 2022). That review also reported that an increase in the zirconia content of a suspension could lead to reduced volumetric shrinkage, whereas it might have challenging effects on factors such as the viscosity and layer thickness.…”
Section: Discussionmentioning
confidence: 99%
“…The mainstream methods for the fabrication of dental objects using digital technologies can be classified into milling and additive manufacturing, which is well known as 3D printing [ 4 , 5 , 6 ]. As reported in previous studies, objects fabricated by milling have advantages in terms of strength and fitting accuracy [ 7 , 8 ], while additive manufacturing can provide objects with minimal cutting material waste at a low cost [ 9 ]. Generally, except for interim prostheses, milling manufacturing is recommended for the fabrication of fixed crowns and bridges that need enough strength and accurate fitting [ 10 ].…”
Section: Introductionmentioning
confidence: 99%